2021
DOI: 10.2147/tacg.s206076
|View full text |Cite
|
Sign up to set email alerts
|

GM1 Gangliosidosis: Mechanisms and Management

Abstract: The lysosomal storage disorder, GM1 gangliosidosis (GM1), is a neurodegenerative condition resulting from deficiency of the enzyme β-galactosidase (β-gal). Mutation of the GLB1 gene, which codes for β-gal, prevents cleavage of the terminal β-1,4-linked galactose residue from GM1 ganglioside. Subsequent accumulation of GM1 ganglioside and other substrates in the lysosome impairs cell physiology and precipitates dysfunction of the nervous system. Beyond palliative and supportive care, no FDA-approved treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 183 publications
(585 reference statements)
0
46
0
1
Order By: Relevance
“…Biomarkers are also essential for monitoring and assessing outcomes in ongoing clinical trials [ 6 ]. Currently, FDA-approved treatments for patients with GM1 gangliosidosis and sialidosis [ 31 , 32 ] are limited to supportive care. The efficacy of substrate reduction therapy, pharmacological chaperones, enzyme replacement therapy, stem cell transplantation, and gene therapy for GM1 gangliosidosis is currently being evaluated [ 6 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers are also essential for monitoring and assessing outcomes in ongoing clinical trials [ 6 ]. Currently, FDA-approved treatments for patients with GM1 gangliosidosis and sialidosis [ 31 , 32 ] are limited to supportive care. The efficacy of substrate reduction therapy, pharmacological chaperones, enzyme replacement therapy, stem cell transplantation, and gene therapy for GM1 gangliosidosis is currently being evaluated [ 6 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The progressive nature of the neurological disease in GM1 gangliosidosis requires close monitoring. Biomarkers in blood, urine, and CSF biomarkers may be potentially useful in this regard (Gray-Edwards et al, 2017a,b;Rha et al, 2021). Disease progression can also be monitored using minimally invasive neuroimaging.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Generalizations based on crystallographic structure of the β-GAL enzyme have been attempted (Ohto et al, 2012). Mutations associated with type I/infantile onset GM1 gangliosidosis, for the most part, are located in the core protein region causing β-gal instability, whereas mutations associated with milder phenotypes, such as types II and III GM1 gangliosidosis, tend to be on the protein surface (Morita et al, 2009;Ohto et al, 2012;Rha et al, 2021). Recently, the determination of the 3D structure of murine β-gal in complex with PPCA has revealed that some mutations at conserved amino acid residues found in GM1 gangliosidosis patients affect formation of the complex (Gorelik et al, 2021).…”
Section: Genotypesmentioning
confidence: 99%
See 2 more Smart Citations